MEMBANGUN KEUNGULAN KOMPETITIF YANG BERKELANJUTAN DI INDUSTRI SEKURITAS MELALUI BLUE OCEAN STRATEGI TERHADAP MAYBANK SEKURITAS - Diana Hartono; Wiliam Santoso (Universitas PGRI Adi Buana, 2026)
Indonesian securities industry experiencing increasingly complex dynamics amid rapid digitalization and financial technology disruption. Growing investor expectations for faster, more efficient, and affordable services are compelling securities firms to innovate strategically. In this context, Maybank Sekuritas Indonesia faces the challenge not only competing within a saturated market but also creating new market space through the integration of the Blue Ocean Strategy. This study aims to analyze the application as means to build sustainable competitive advantage in the securities industry. The research focuses on digital service innovation, through the transformation of stock trading applications designed to provide financial education, intelligent analytics, and personalized user experiences. With qualitative case study method and a descriptive-analytical approach, data are collected through in-depth interviews, internal document analysis, and literature review related to innovation strategy and capital market management. The expected outcome of this study is a conceptual model of Blue Ocean Strategy integration relevant to Indonesia’s securities industry. This model is intended to serve as a framework for creating new value (value innovation), strengthening investor loyalty, and enhancing long-term corporate competitiveness. Academically, the findings contribute to the development of theories on strategic innovation and in the digital financial services sector.